(untitled) (Música Hodie, 2025)
The use of elements of gamification in education, as well as video or audio materials that are attractive to students, is one of the most common ways to increase student engagement in learning. The purpose of this study is to analyze the impact of using gamification and music in the process of learning a foreign language. The study uses focus group discussions and pre- and post-testing to determine the level of language proficiency. After completing the program, the results showed a significant increase in the number of students with high language levels - 18 students (after the previous test there were 12), which is 30%. There number of middle-level students increased to 36 (60%), and 6 students still were at a low level, which is 10%. The results showed changes in the student’s motivation and attitude. In ining program. The levparticular, 53 students (88%) expressed their admiration and positive feelings after completing the trael of student motivation has increased significantly (45 students in the 6-7 range on the scale), which indicates that the use of gamified programs and elements in the educational process contributes to increasing student motivation and involvement in the educational process. The practical value of this study lies in increasing understanding of how elements of gamification combined with music-based learning affect learning outcomes and motivation. Educational institutions can use such a technique to improve the success and effectiveness of students in learning English. The use of this program can contribute to increasing students’ motivation, which is an extremely important factor for the success of language learning.